Uterine overdistention induces preterm labor mediated by inflammation: observations in pregnant women and nonhuman primates - Waldorf,KMA; Singh,N; Mohan,AR; Young,RC; Ngo,L; Das,A; Tsai,J; Bansal,A; Paolella,L; Herbert,BR; Sooranna,SR; Gough,M; et al. (American Journal of Obstetrics and Gynecology, 2015)
ObjectiveUterine overdistention is thought to induce preterm labor in women with twin and multiple pregnancies, but the pathophysiology remains unclear. We investigated for the first time the pathogenesis of preterm birth associated with rapid uterine distention in a pregnant nonhuman primate model.Study DesignA nonhuman primate model of uterine overdistention was created using preterm chronically catheterized pregnant pigtail macaques (Macaca nemestrina) by inflation of intraamniotic balloons (N = 6), which were compared to saline controls (N = 5). Cesarean delivery was performed due to preterm labor or at experimental end. Microarray, quantitative reverse transcriptase polymerase chain reaction, Luminex (Austin, TX), and enzyme-linked immunosorbent assay were used to measure messenger RNA (mRNA) and/or protein levels from monkey (amniotic fluid, myometrium, maternal plasma) and human (amniocytes, amnion, myometrium) tissues. Statistical analysis employed analysis of covariance and Wilcoxon rank sum. Biomechanical forces were calculated using the law of Laplace.ResultsPreterm labor occurred in 3 of 6 animals after balloon inflation and correlated with greater balloon volume and uterine wall stress. Significant elevations of inflammatory cytokines and prostaglandins occurred following uterine overdistention in an “inflammatory pulse” that correlated with preterm labor (interleukin [IL]-1β, tumor necrosis factor [TNF]-α, IL-6, IL-8, CCL2, prostaglandin E2, prostaglandin F2α, all P < .05). A similar inflammatory response was observed in amniocytes in vitro following mechanical stretch (IL1β, IL6, and IL8 mRNA multiple time points, P < .05), in amnion of women with polyhydramnios (IL6 and TNF mRNA, P < .05) and in amnion (TNF-α) and myometrium of women with twins in early labor (IL6, IL8, CCL2, all P < .05). Genes differentially expressed in the nonhuman primate after balloon inflation and in women with polyhydramnios